2003
DOI: 10.5703/1288284313165
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Tire Shreds Test Embankment

Abstract: Prepared in cooperation with the Indiana Department of Transportation and Federal Highway Administration. AbstractAccording to recent research, it is estimated that there are more than 500 million tires stockpiled across the United States, and 270 million more are generated each year. A significant number of tires are left in empty yards and even dumped illegally. Tires have characteristics that make them not easy to dispose, and potentially combustible. For these reasons, there is a strong need to find benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
(7 reference statements)
1
8
0
Order By: Relevance
“…The other case study data presented in Fig. 11 ͑i.e., Tweedie et al 1998;Humphrey et al 2000;Dickson et al 2001;Salgado et al 2003;Hoppe and Mullen 2004͒ largely corroborates with the magnitude and trends in the laboratory data, suggesting that the results of this experimental study can be reliably extrapolated to large prototype TDA structures.…”
Section: Discussion and Practical Implicationssupporting
confidence: 80%
See 1 more Smart Citation
“…The other case study data presented in Fig. 11 ͑i.e., Tweedie et al 1998;Humphrey et al 2000;Dickson et al 2001;Salgado et al 2003;Hoppe and Mullen 2004͒ largely corroborates with the magnitude and trends in the laboratory data, suggesting that the results of this experimental study can be reliably extrapolated to large prototype TDA structures.…”
Section: Discussion and Practical Implicationssupporting
confidence: 80%
“…Accordingly, studies have evaluated the compressibility characteristics of TDA and TDA composites ͑e.g., Ahmed 1993;Edil and Bosscher 1994;Tatlisoz et al 1997͒. Most of these studies have focused on evaluating immediate compressibility; however, case histories have clearly shown that when used in geotechnical applications TDA and TDA composites continue to deform over time periods that extend well beyond the initial application of load ͑e.g., Bosscher et al 1993;Tweedie et al 1998;Humphrey et al 2000;Dickson et al 2001;Hoppe and Mullen 2004;Salgado et al 2003;Zornberg et al 2004b͒. These time-dependent deformations occur at a generally constant rate over logarithmic cycles of time and can approach strains of 5% or more after 1 to 2 years ͑Fig.…”
Section: Introductionmentioning
confidence: 99%
“…From a more practical point of view, rubber and sand mixed in equal proportion were used to form the 2 m height embankment core in the State Road 31 in Lakeville, USA (Salgado et al 2003;Yoon et al 2005). After 200 days of ordinary traffic only 12 mm of settlement were detected and there were no problems of stability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For this reason, many experimental and field studies have been performed on the environments and fluids which are placed next to these materials. The obtained results show that no harmful effect is relevant and the only environmental limitation in the use of crumb rubber is related to their self-ignition potential [1][2][3][4]. In1998, the ASTM regulation provided the D6270 instruction to decrease this potential.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the solutions are reusing them as filler materials in construction projects, such as road construction, retaining walls, and drainage systems. Over the past two decades, several studies have been conducted about the application of crumb rubber in the reinforcement of retaining earth walls and also about its use as filler materials in the road construction [1][2][3]. In addition to using crumb rubber in geotechnical projects, it is important to pay attention to possible environmental pollutions caused by these material types.…”
Section: Introductionmentioning
confidence: 99%